Hubungan Pendayagunaan Kaum Muda dalam Bidang Pelayanan terhadap Pertumbuhan Rohani Kaum Muda di Gereja Reformasi Yerusalem Noelbaki - Dominggus Umbu Dingu; Elisabeth Dethan; Petrus Kefas Loka (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
By looking at the existing generations, it is very important to describe the great figures who were diligent in preparing generations, namely Moses educating Joshua in preparing the command of the line to go on a long journey, the same thing was done by Elijah by diligently educating professional cadres, namely Elisha, even the Lord Jesus too. He was active in educating his students and Paul was educating Timothy. This reminds us again that the Church should never neglect its obligations to young people because the risk is too dangerous, because the church will lose its strength, and even lose its young people. The study of science may give rise to doubt in the hearts of young people who are developing, because it seems like it is not in line with God's Word. True science will not conflict with the Bible, because scientific laws are from God and He is the one who inspired what is written in the Bible. The theories put forward by scholars may conflict with each other, or may provide incorrect interpretations of the Bible. According to the educational dictionary, methods mean ways and procedures for carrying out an activity to achieve goals effectively. And research aims to reveal phenomena in the field or in society so that they are clearly known and can be used as a basis for developing all kinds of needs for human life. rstabel Spearman with α = 5% and n = 9, then rstabel = 0.683 and from rstabel and rstabel it can be seen that rstabel ˂ rstabel is 0.658˂ 0.683 so it can be known for certain that Hi is rejected and Ho is accepted. This means there is no significant relationship between variable X (Counselor) and variable Y (student learning achievement). The regression coefficient is 0.482, meaning that each addition (because of the + sign) of one Counselor score will give an increase in score of 0.482. So, counselors can influence student learning achievement by 36.3%. The main foundation of the teachings disseminated to students by Christian Religious Education (PAK) teachers is the Bible, which is contained in II Timothy 3:16, so that teaching in the form of theory and practice must not deviate from this path. As a Christian Religious Education teacher, you must maintain that your teaching comes from God. With the aim of spreading the truth of God's Word (Matthew 28:19-20).